PERADABAN ISLAM DI KOTA TEBING TINGGI - Juliet Medi Anda (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2021)
In writing this journal aims to find out the history and civilization of Islam in the cliff town of North Sumatra, in a context that focuses on aspects of aspects and monuments in the city of high cliffs as evidence of Islamic civilization in the city of high cliffs. The study of Islamic civilization in Tebing Tinggi is important because based on its history, Tebing Tinggi was once a kingdom before becoming an autonomous region. The period of Dutch rule in East Sumatra or Dutch colonialism (Hindia Holland) applies in East Sumatra since the signing of the conflict contract between the Dutch. and siak on February 1, 1858. In this agreement it is stated that the kingdom of Siak Sri Indrapura and its colonies and conquests were under the Dutch Sultanate and became part of the Dutch East Indies. The method used is the historical method. The results of this study show the development of the development of Islamic civilization in Tebing Tinggi, divided into several periods, namely the historical period of the high cliff city, the existence of a figure who can be said to be the founder of the high cliff city, and the kingdom of the land of Padang which was the forerunner of the birth of the high cliff city.